ANALISIS DAMPAK LINGKUNGAN, SOSIAL, EKONOMI UNIT USAHA PENGELOLA SAMPAH DI DESA GUWOSARI, DAERAH ISTIMEWA YOGYAKARTA - Bayu Seto; Mustika Kamaluddin (DAS Institute, 2023)
According to data from the Ministry of Environment and Forestry of the Republic of Indonesia, in 2022 there will be 25.93 million tons of household waste generation. The approach to waste management is an aspect that must be considered in order to reduce the level of unmanaged waste by involving the the community in order to reduce the amount of waste generation. DIY province is one of the areas that is actively carrying out campaigns for independent waste management, one of which is the Guwosari Village. To measure business feasibility, it is necessary to evaluate 1) the economic value added of waste management, and 2) the social-environmental impact of waste management. This study uses a qualitative approach, with data collection methods in the form of 1) observation, 2) interviews, and 3) document analysis. The data obtained were then analyzed using 1) cost-benefit analysis to measure economic value added, and 2) values ​​in eco-efficiency and TBL to measure the social-environmental impact of waste management activities. The results of the study show that 1) economic added value is experiencing a negative trend due to suboptimal projected activities and empowerment of human resources, and 2) the achievement of social-environmental impacts already fulfills some of the principles/values ​​in TBL and eco-efficiency, but an assessment needs to be carried out further related to mitigating social-environmental risks that have the potential to arise in the future.